Global Trends and Impacts of Gamification Iin Language Learning: A Bibliometric Analysis - Taqdir, Taqdir (Lingua Cultura, 2024)
This study investigates global trends and impacts of gamification in language learning, focusing on how research in this area has evolved over the past two decades (2000–2024). A bibliometric approach was adopted, utilizing data from the Scopus database and applying the PRISMA framework to systematically identify and include 358 relevant articles. The study employed bibliometric tools, VOSviewer and Bibliometrix, to analyze collaboration networks, keyword associations, and publication trends. The findings reveal significant global growth in gamification research, with a sharp increase in publications between 2015 and 2020, driven by advancements in digital learning technologies. Countries such as the United States, Spain, Indonesia, and Malaysia emerged as key contributors. Gamification was shown to enhance motivation, engagement, and learning outcomes, particularly in vocabulary and grammar instruction, while its impact on speaking skills remains underexplored. Cultural, technological, and policy factors were found to influence the adoption of gamification, suggesting that localized strategies are essential for effective implementation. This study offers original insights into the global development and application of gamification in language learning and highlights gaps that require further exploration, such as its use in advanced language skills and technology-limited settings. The findings provide practical implications for educators, curriculum developers, and policymakers to design inclusive and adaptive gamification strategies that address diverse educational contexts.